The impact and utilisation of patient-initiated follow-ups (PIFU) in the elective upper-limb clinic at secondary care - R Naskar; V Garg; E Middleton; R Moverley (The Annals of The Royal College of Surgeons of England, 2026)
Background Musculoskeletal (MSK) conditions affect over 20 million people in the UK. Follow-up appointments account for nearly two-thirds of all outpatient activity. Patient-initiated follow-up (PIFU) allows patients to request follow-up appointments based on clinical need, aiming to reduce unnecessary reviews and optimise service use. This study evaluated the impact and utilisation of PIFU in a secondary care Elective Upper Limb (Shoulder and Elbow) Clinic, focusing on patient engagement, re-presentation rates, and suitability across common upper limb conditions. Methods A retrospective service evaluation was conducted over 18 months. Patients discharged under the PIFU pathway were included if they had at least six months’ follow-up opportunity. Data collected included diagnosis, treatments received, re-presentation rates and outcomes. Descriptive analysis was used to assess patterns and clinical implications. Results Out of 353 consultations, 81 patients (23%) were discharged to PIFU. Among these, 62% were first-time referrals discharged at their initial appointment. Conditions most suitable were rotator cuff-related pain (33%), early glenohumeral arthritis (19%) and adhesive capsulitis (10%). Within six months, only 18% of PIFU patients re-accessed care – just 4.2% of the total cohort. One-third of returning patients required surgery, while the remainder were managed nonoperatively and re-entered the PIFU pathway. PIFU freed approximately 20% of follow-up slots. Conclusions PIFU is a safe and effective follow-up model for stable or early-stage shoulder and elbow conditions, reducing outpatient burden, supporting patient autonomy and preserving clinic capacity without compromising care quality. Broader implementation, supported by patient education and structured feedback, may enhance sustainable delivery of orthopaedic services.